2007
DOI: 10.1055/s-2007-984498
|View full text |Cite
|
Sign up to set email alerts
|

Selective Aerobic Oxidation of Allylic Alcohols to Carbonyl Compounds Using Catalytic Pd(OAc)2: High Intramolecular Selectivity

Abstract: Allylic alcohols were selectively oxidized into aldehydes or ketones using a Pd(OAc) 2 -Et 3 N-O 2 system. Diols with one allylic function were selectively oxidized, with one of the hydroxyl groups remaining untouched.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Additionally, we observed that the absolute configuration of vitexins 1 and 6 is drawn and/or stated to be (7 S ,8 R )-configuration with a reported large levorotatory rotation ([a] 20 D = −176.0° ( c 0.5, MeOH)) which is inconsistent with other, nonaldehyde, levorotatory dihydronaphthalene lignans which are commonly (7 R , 8 S ). We therefore wished to develop an enantioselective method to synthesize dihydro-naphthalane aldehyde-alcohol lignans, which would allow for determination of the absolute configuration of the natural products.…”
mentioning
confidence: 99%
“…Additionally, we observed that the absolute configuration of vitexins 1 and 6 is drawn and/or stated to be (7 S ,8 R )-configuration with a reported large levorotatory rotation ([a] 20 D = −176.0° ( c 0.5, MeOH)) which is inconsistent with other, nonaldehyde, levorotatory dihydronaphthalene lignans which are commonly (7 R , 8 S ). We therefore wished to develop an enantioselective method to synthesize dihydro-naphthalane aldehyde-alcohol lignans, which would allow for determination of the absolute configuration of the natural products.…”
mentioning
confidence: 99%
“…Direct selective oxidation of the benzylic hydroxyl group in S1 was carefully pursued; however, an array of attempts ( e.g. , CHDFe(CO) 3 /Me 3 NO, 22 Pd(OAc) 2 /TEA/O 2 , 23 MnO 2 , 24 and Ag 2 CO 3 ) proved to be unsuccessful. Thus, selective silylation of the primary hydroxyl group of S1 with TIPSCl followed by oxidation with Dess–Martin periodinane (DMP) generated 23 25 as a colorless oil in 69% yield over three steps from 8 .…”
mentioning
confidence: 99%